The Relationships among Customer Value, Satisfaction and Behavioral Intentions: A General Structural Equation Model - Wahyuningsih Wahyuningsih (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2005)
The objective of this paper is to present a comprehensive framework of relationships among customer value, satisfaction, and behavioral intentions. Before testing the model, literature review on the three constructs is presented. From this review, three hypotheses are proposed and tested in this study: (1) Customer value is antecedent to customer satisfaction, (2) Customer value has a direct link to behavioral intentions, and (3) The relationship between customer value and behavioral intentions is mediated by customer satisfaction. Structural Equation Modeling using AMOS 5 was employed to test the model. The result suggests that the relationship between customer value and behavioral intentions is mediated by customer satisfaction.